2016
DOI: 10.1097/mpg.0000000000001384
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Calprotectin in Treated and Untreated Children With Coeliac Disease and Juvenile Idiopathic Arthritis

Abstract: This study aimed to provide evidence on whether children at risk of gastrointestinal inflammation have increased measurements of faecal calprotectin (FC). Faecal calprotectin was measured in 232 children; 55 children (n=11 treatment naïve) with juvenile idiopathic arthritis (JIA), 63 with coeliac disease (CD); 17 with new diagnosis before and after treatment on gluten free diet and 114 controls. None of the treatment-naive children with JIA had raised FC. Four JIA patients on treatment had a raised FC but in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…Intestinal atrophy seems to be a dominant feature influencing the FC levels in CD patients (15). Here, we detected markedly higher FC levels in the patients that all had villous atrophy (Marsh score 3) while previous reports incorporated children with lower Marsh scores (4,11,15). However, FC was associated with neither the grade of intestinal inflammation nor with the clinical picture of CD in a report by Montalto et al (17).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Intestinal atrophy seems to be a dominant feature influencing the FC levels in CD patients (15). Here, we detected markedly higher FC levels in the patients that all had villous atrophy (Marsh score 3) while previous reports incorporated children with lower Marsh scores (4,11,15). However, FC was associated with neither the grade of intestinal inflammation nor with the clinical picture of CD in a report by Montalto et al (17).…”
Section: Discussioncontrasting
confidence: 45%
“…In a recent report, children with total villous atrophy showed higher FC levels (13.8 ± 9.3 mg/L) than those with partial atrophy (3.7 ± 1.8 mg/L) (15). Similarly, 17 children newly identified with CD had higher FC levels than healthy children (11). According to the report by Tola et al (16), the mean value of FC was significantly higher in adults with CD than in healthy ones.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly to the aforementioned study, Balamtekin et al [8] confirmed significantly higher FCC in untreated children with CD in comparison with treated children and with the control group (p < 0.001). In a group of 63 children with recently diagnosed CD, studied by Biskou et al [9], patients with CD had higher FCC than their healthy peers (36.4 mg/kg vs. 25 mg/kg).…”
Section: Discussionmentioning
confidence: 96%
“…However, data on FC levels in the assessment of intestinal inflammation among patients with JIA are limited. Although Biskou, et al12 found that FC levels are not raised in children with JIA, it has been demonstrated that FC levels could be higher in JIA patients because of their use of nonsteroidal antiinflammatory drugs; however, levels returned to normal values after drug withdrawal13 . Stoll, et al found that FC levels were higher in children with ERA if compared to patients with nonspondyloarthritis subtype and unrelated connective tissue diseases, and noninflammatory control subjects…”
mentioning
confidence: 98%